La transición alimentaria y nutricional de la infancia en Ecuador: un enfoque pluralista y pragmático - Jairo Rivera (L'Ordinaire des Amériques)
The global food and nutrition transition is framed in the coexistence of child undernutrition and child overweight, where each country and locality has its own level of prevalence. The objective of this research is to analyze the food and nutrition transition of children in Ecuador through a pluralistic and pragmatic approach associated with Boltanski's "cities" (2006). For this purpose, a mixed methodology is used based, on the one hand, a quantitative approach, on the databases of the national child nutrition surveys and, on the other hand, a qualitative approach, on primary information collected during field work in the provinces with the highest prevalence of malnutrition in the country. Among the main results, it is found that the food and nutrition transition is associated with changes in consumption habits, limited practice of breastfeeding and the persistence of structural barriers such as poverty.